Solusi Rantai Pasokan Berbasis Blockchain Menggunakan Teknologi IPFS dan QR untuk Tenun Tradisional di Nusa Tenggara Barat - Heri Wijayanto; Melki Jonathan Andara; Diky Wiraguna; Nadiyasari Agitha; Mosiur Rahaman (JURNAL INFOTEL, 2024)
Traditional weaving is a significant cultural heritage in West Nusa Tenggara, Indonesia, renowned for its unique and intricate woven fabrics. However, the industry faces challenges such as product counterfeiting and the need for more transparency in the supply chain, hindering its growth and economic potential. This paper proposes a solution by leveraging blockchain technology to enhance traceability, security, and efficiency throughout the supply chain of traditional woven products. Integrating the InterPlanetary File System (IPFS) and Quick Response (QR) codes further fortifies data integrity and provides consumers with comprehensive product information. A prototype web application is developed, demonstrating the practical implementation of this framework. Rigorous testing of the prototype validates the correct functionality of the proposed solution. This innovative framework aims to safeguard the authenticity and sustainability of the traditional woven products from West Nusa Tenggara, fostering a more competitive and secure industry while preserving cultural heritage.